A presença do urbano no espaço rural: um desafio para a pastoral da Arquidiocese de Pouso Alegre - Santos, Douglas Aparecido Marques Rocha dos (2014)
This study aims to analyze the dialogue between Urban Culture and Rural Culture and its consequences for pastoral action, in order to find out and to work the presence in the urban rural areas of the Archdiocese of Pouso Alegre. These elements reveal the challenges to evangelization, the proposed work and the necessity for a deeper understanding of reality. Considering the input these elements rural urban context arises to need to ask if it is possible to use these elements in pastoral work. For this study will need a secure knowledge of the reality of ecclesial division: their training, configuration, their context, their history and challenges. Furthermore it will be important to resort on theoretical literature knowledge to make conceptual understanding of certain elements, such as: rural, town, urban, new evangelization, knowledge of reality. All of this it will foster not only a perception of reality, but show that it is possible to make use of these elements of parish pastoral